Drug-coated balloon angioplasty in failing haemodialysis arteriovenous shunts: 12-month outcomes in 200 patients from the Aperto Italian registry. Issue 6 (November 2019) - Tozzi, Matteo; Franchin, Marco; Savio, Daniele; Comelli, Simone; Di Maggio, Luca; Carbonari, Luciano; Ebrahimi, Reza; Fontana, Federico; Piacentino, Filippo; Cervarolo, Maria Cristina; Palermo, Vincenzo; Piffaretti, Gabriele
Background: We evaluated the safety and technical and clinical outcomes of angioplasty with a drug-coated balloon for the management of venous stenosis in arteriovenous grafts and arteriovenous fistulas in patients undergoing haemodialysis. Methods: Data were obtained from an ongoing prospective, non-randomised registry conducted at three Italian centres. Patients were treated with a drug-coated balloon according to standard procedures in each participating centre. Evaluation was by colour Doppler imaging every 3 months. The primary end-point was primary assisted patency. The secondary end-point was the rate of assisted patency of the vascular access. Results: A total of 311 angioplasty procedures in 200 patients, (60.4% male), were analysed. The procedural success rate was 100%. A total of 192 treatments of restenosis were necessary in 81 patients during average 21 ± 8 months follow-up. Kaplan–Meier estimates indicated that 88.0%, 64.2% and 40.6% of treated lesions were free from restenosis at 6, 12 and 24 months, respectively. Including multiple angioplasty, circuit patency rates were 99.2%, 92.5% and 84.8% at 6, 12 and 24 months, respectively. Primary patency rates were highest in shunts treated de novo with drug-coated balloons. Risk of restenosis was associated with circuit age (p = 0.017), history of treatment with conventional angioplasty (p < 0.001) and the kind of balloon used during pre-dilation (p = 0.001). Conclusion: The results suggest that favourable long-term patency rates can be achieved with the drug-coated balloon in a varied population of patients with failing haemodialysis arteriovenous shunts treated under conditions of actual care.